Dry versus hydrated collagen scaffolds: are dry states representative of hydrated states? - Suchý, Tomáš; Šupová, Monika; Bartoš, Martin; Sedláček, Radek; Piola, Marco; Soncini, Monica; Fiore, Gianfranco Beniamino; Sauerová, Pavla; Kalbáčová, Marie Hubálek (Journal of materials science. Materials in medicine, 2018)
Collagen composite scaffolds have been used for a number of studies in tissue engineering. The hydration of such highly porous and hydrophilic structures may influence mechanical behaviour and porosity due to swelling. The differences in physical properties following hydration would represent a significant limiting factor for the seeding, growth and differentiation of cells in vitro and the overall applicability of such hydrophilic materials in vivo. Scaffolds based on collagen matrix, poly(DL-lactide) nanofibers, calcium phosphate particles and sodium hyaluronate with 8 different material compositions were characterised in the dry and hydrated states using X-ray microcomputed tomography, compression tests, hydraulic permeability measurement, degradation tests and infrared spectrometry. Hydration, simulating the conditions of cell seeding and cultivation up to 48 h and 576 h, was found to exert a minor effect on the morphological parameters and permeability. Conversely, hydration had a major statistically significant effect on the mechanical behaviour of all the tested scaffolds. The elastic modulus and compressive strength of all the scaffolds decreased by ~95%. The quantitative results provided confirm the importance of analysing scaffolds in the hydrated rather than the dry state since the former more precisely simulates the real environment for which such materials are designed.
Keywords: pevnost v tlaku; Tissue Engineering; Mechanical Phenomena; Calcium Phosphates; tkáňové inženýrství; Polyesters; poréznost; testování materiálů; fosforečnany vápenaté; modul pružnosti; Tissue Scaffolds; kolagen; Collagen; Elastic Modulus; Biocompatible Materials; Compressive Strength; vysoušení; rentgenová mikrotomografie; polyestery; mechanické jevy; tkáňové podpůrné struktury; voda; kyselina hyaluronová; X-Ray Microtomography; Porosity; Water; biokompatibilní materiály; Hyaluronic Acid; Desiccation; Materials Testing